Answer:
so b=-9 while c=12.
Step-by-step explanation:
If you have x-intercepts 1 and -4, then that means f(1)=0 and f(-4)=0.
You are given [tex]f(x)=-3x^2+bx+c[/tex]
So you have the system of equations to solve:
[tex]f(1)=-3(1)^2+b(1)+c=0[/tex]
[tex]f(-4)=-3(-4)^2+b(-4)+c=0[/tex]
Evaluating the exponents:
[tex]-3(1)+b+c=0[/tex]
[tex]-3(16)-4b+c=0[/tex]
Doing a little bit of multiplying:
[tex]-3+b+c=0[/tex]
[tex]-48-4b+c=0[/tex]
Let's add 3 on both sides of equation 1 and 48 on both sides of equation 2:
[tex]b+c=3[/tex]
[tex]-4b+c=48[/tex]
Subtracting the equations will eliminate c.
Let's do that:
[tex]5b+0c=-45[/tex]
[tex]5b=-45[/tex]
Divide both sides by 5:
[tex]b=\frac{-45}{5}[/tex]
Simplify:
[tex]b=-9[/tex]
If b=-9 and b+c=3 then -9+c=3 implies c=9+3=12.
so b=-9 while c=12.
To find b and c for the parabola y=-3x^2+bx+c with x-intercepts 1 and -4, we express the equation in its factored form, then expand it. From the expansion, we see that b=-9 and c=-12.
Explanation:To find the values of b and c in the equation y = -3x^2+bx+c, where the x-intercepts are given as 1 and -4, we use the following steps:
Realize that a parabola that crosses the x-axis at points 1 and -4 can be expressed in the factored form y = -3(x - 1)(x + 4). Expand this factored form: y = -3x^2 - 9x - 12. From this expansion, we can identify that b = -9 and c = -12.Learn more about Quadratic Equation here:
https://brainly.com/question/26090334
#SPJ2
What is the value of x in the equation 4x + 8y - 40, when y-0.8?
4.6
0 8.4
Answer:
8.4
Step-by-step explanation:
the equation 4x+8y -40 can be written as 4x-8y-40=0, this represents a line in a space of two dimensions.
solving for x when y=0.8 we have the equation below>
[tex]4x+8*0,8-40=0[/tex]
Which gives that x=42/5, or in more simpler terms, 8.4
The area of a circle is 36π. What is the length of a diameter of the circle?
Answer:
d =12
Step-by-step explanation:
The area of a circle is given by
A = pi r^2
Substituting what we know
36 pi = pi r^2
Divide each side by pi
36 pi/pi = pi r^2/pi
36 = r^2
Taking the square root of each side
sqrt(35) = sqrt(r^2)
6 =r
We want the diameter
d = 2r
d = 2(6)
d = 12
What are the values of a and b?
a = 14, b = 6
a = 14, b = 8
a = 17, b = 6
a = 17, b = 8
According to the question the values of a and b are 17 and 6 respectively
What is a kite?A kite is a quadrilateral that has 2 pairs of equal-length sides and these sides are adjacent to each other.
According to the Definition:
Sides FJ = HJ ( from the diagram)
Hence (3b + 6) = 24cm
3b = 24 - 6
3b = 18
b = 6
Sides FG = GH (from the diagram)
(2a - 4) = 30
2a = 30 + 4
a = 34/2
a = 17
Hence the value of a and b are 17 and 6 respectively.
Learn more about quadrilaterals on:
https://brainly.com/question/1190071
#SPJ2
Answer: C
Step-by-step explanation:
Consider the combined function. f(X) + g(X) = 9x + 4 . If f(x) = 4x - 3, find g(x)
Answer:
g(x)=5x+7
Step-by-step explanation:
f(x)+g(x)=9x+4
We are given f(x)=4x-3.
So we insert 4x-3 for f:
4x-3+g(x)=9x+4
Subtract 4x on both sides:
-3+g(x)=5x+4
Add 3 on both sides:
g(x)=5x+7
Check:
f(x)+g(x)
=(4x-3)+(5x+7)
=(4x+5x)+(-3+7)
=(9x) +(4)
=9x+4
Bingo. We did it! :)
The function g(x) can be found by rearranging the equation f(X) + g(X) = 9x + 4 and substituting f(x) = 4x - 3 into it. This leads to g(x) = 5x + 7.
Explanation:The given combined function is f(X) + g(X) = 9x + 4 and we know that f(x) = 4x - 3. To find g(x), we need to rearrange the combined function to make g(x) the subject. So step 1: subtract f(x) from both sides of the equation, giving: g(x) = 9x + 4 - f(x).
Then, we substitute f(x) into the equation, resulting in: g(x) = 9x + 4 - (4x - 3). Simplifying this gives us g(x) = 9x + 4 - 4x + 3, which further simplifies to g(x) = 5x + 7. This is the function g(x).
Learn more about Function here:https://brainly.com/question/35114770
#SPJ2
Elise picks 6 pounds of apples.She uses 1/2 pounds to make 1 container of apple sauce. How many containers of applesauce can Elise make with all apples?
Answer:
12 Containers
Step-by-step explanation:
given it takes 1/2 a pound to make one container, we can deduce:
1 pound makes 2 containers
2 pounds makes 4 containers
thus the amount of containers is equal to 2x (x being pounds of apples picked)
so
2(6)=12
Elise can make 12 containers of applesauce. Here's how to calculate it:
Step 1: Determine the total amount of apples Elise has:
Elise has picked 6 pounds of apples.
Step 2: Identify how many pounds of apples are needed for one container of applesauce:
According to the information provided, 1/2 pound of apples is needed to make 1 container of applesauce.
Step 3: Calculate how many containers Elise can make:
To find out how many containers of applesauce Elise can make, divide the total pounds of apples by the pounds of apples per container.
The calculation is as follows:
6 pounds of apples ÷ (1/2) pound per container = 12 containers
Therefore, with 6 pounds of apples, Elise can make 12 containers of applesauce.
Which value for y makes the sentence true? 8 - y = 9 - 3
Answer:
y=2
Step-by-step explanation:
8 - y = 9 - 3
Combine like terms
8 - y = 6
Subtract 8 from each side
8-8 - y = 6-8
-y = -2
Multiply each side by -1
-1 * -y = -2 *-1
y =2
Divide 27x3 - 72x2 + 36x by 9x.
Answer:
3x^2 - 8x + 4.
Step-by-step explanation:
Dividing each term by 9x we get:
3x^2 - 8x + 4.
As per cubic equation, the result is [tex](3x^{2}-8x+4)[/tex].
What is a cubic equation?A cubic equation is an equation where the highest power of the variable is 3.
The given linear equation is:
[tex]\frac{27x^{3}- 72x^{2}+ 36x}{9x} \\= \frac{27x^{3}}{9x} -\frac{72x^{2}}{9x}+\frac{36x}{9x}\\ = 3x^{2}-8x+4[/tex]
The result is [tex](3x^{2}-8x+4)[/tex].
Learn more about cubic equation here: https://brainly.com/question/1282396
#SPJ2
The perimeter of ΔABC is 13 cm. It was dilated to create ΔA'B'C'. What is the perimeter of ΔA'B'C'? 13 cm 26 cm 39 cm 52 cm
Answer:
The answer is 52
Step-by-step explanation:
We need figure out the dilated by doing OB’/OB. 5+15= OB’. OB’ = 20. We already know that OB is 5. We used the substitution property. 20/5 = 4. Now, we got 4 as dilation. 13 cm x 4 = 52 cm. Therefore, our answer is 52
Perimeter of ΔA'B'C' is 52 cm.
The perimeter of ΔABC is =13 cm
Length of OB = 5 cm
Length of OB' = 15 + 5 = 20 cm
The Dilation factor can be found out b
ΔOCB and ΔOC'B' are similar as BC|| B'C'
From triangles ΔOCB & ΔOC'B' the dilation factor can be found out
by the formula below
[tex]\frac{BC}{B'C'} = \frac{5}{20}[/tex]
B'C'= 4[tex]\times[/tex]BC
so the dilation factor = 4
hence the new perimeter of the triangle = 13 [tex]\times[/tex] 4 = 52 cm
for more information please refer the link below
https://brainly.com/question/20502441
nala wants to determine if x-5 is a factor of p(x)=x^3-5x^2-x+5. Help Nala organize her steps.
Step 1-?
Step 2-?
Step 3-?
options:
1) apply the factor theorem, the remainder is 0 so x-5 is a factor of p(x)
2) apply the factor theorem, the remainder is not 0 so x-5 is not a factor of p(x)
3) evaluate p(x) for x=5
4) apply the polynomial theorem, the remainder is 0, so x-5 is a factor of p(x)
5) divide
6) simplify and find the remainder
7) evaluate p(x) for x=-5
Answer:
I only used two steps: 3) then 6) then 1).
Step-by-step explanation:
Ok, if x-5 is a factor of p(x), then p(5)=0 by factor theorem.
This also goes the other way around:
If p(5)=0 then x-5 is a factor of p(x) by factor theorem.
Let's check. I'm going to evaluate p(x) for x=5.
[tex]p(5)=5^3-5(5)^2-5+5[/tex]
[tex]p(5)=125-5(25)-5+5[/tex]
[tex]p(5)=125-125-5+5[/tex]
[tex]p(5)=0+0[/tex]
[tex]p(5)=0[/tex]
This implies x-5 is a factor since we have p(5)=0.
The first step I did was 3) evaluate p(x) for x=5.
The second step I did 6) simplify and find the remainder. I did this when I was evaluating p(5); that was a lot of simplification and then I found the remainder to be 0 after that simplification. The last step was 1) apply the factor theorem, the remainder is 0 so x-5 is a factor of p(x).
To determine if x-5 is a factor of the polynomial, evaluate p(x) when x=5. If the result is 0, then the Factor Theorem implies that x-5 is a factor. If not, x-5 is not a factor.
Explanation:To determine if x-5 is a factor of p(x)=x^3-5x^2-x+5, you can follow these steps:
When you evaluate p(x) for x=5, if you get 0, it demonstrates, according to the factor theorem, that x-5 is a factor of p(x) because it results in the polynomial function equaling zero. If you don't get zero, then it's not a factor.
Learn more about the Factor Theorem here:https://brainly.com/question/35460223
#SPJ3
Which equation produces a line that is parallel to the line represented by the function below?
y= 2/5x + 9
A. y= 5x + 2y = 4
B. y= 2x - 5y = 8
C. y= 5x - 2y = -3
D. y= 2x + 5y = -7
Answer:
B.
I ignored the extra y= part in each equation.
Step-by-step explanation:
The line given is in slope-intercept form, y=mx+b where m is slope and b is y-intercept.
Parallel lines have the same slope.
So the slope of y=(2/5)x+9 is m=2/5.
So we are looking for a line with that same slope.
In slope-intercept form the line would by y=(2/5)x+b where we do not know b since we weren't given a point.
So all of the choices are written in standard form ax+by=c where a,b, and c are integers.
We want integers so we want to get rid of that fraction there. To do that we need to multiply both sides of y=(2/5)x+b for 5. This gives us:
5y=2x+5b
Subtract 2x on both sides:
-2x+5y=5b
Now of the coefficients of x in your choices is negative like ours is. So I'm going to multiply both sides by -1 giving us:
2x-5y=-5b
Compare
2x-5y=-5b to your equations.
A doesn't fit because it's left hand side is 5x+2y.
B fits because it's left hand side is 2x-5y.
C doesn't fit because it's left hand side is 5x-2y.
D doesn't fit because it's left hand side is 2x+5y.
I ignored all the extra y= parts in your equations.
Find a if b=5 and c=8cm
Using the Pythagorean theorem:
a = √(c^2 - b^2)
a = √(8^2 - 5^2)
a = √(64 - 25)
a = √39 ( Exact answer )
Or √39 = 6.244997 as a decimal and you round the decimal answer as needed.
A sphere and a cylinder have the same radius and height. The volume of the cylinder have the same height and radius. The volume of the cylinder is 27pi ft. What equation gives the volume of the sphere ?
The equation of the volume of the sphere is 4/3 × 27π
The volume of a cylinder is expressed as
V = πr²h
Since the cylinder has thesame height and radius, therefore, the volume of the cylinder will now be
V = πr² × r
V = πr³
The volume of a sphere is expressed as
V = 4/3(πr³)
Therefore we can say
the volume of sphere = 4/3 × volume of the cylinder
Volume of cylinder = 27π
volume of sphere = 4/3 × 27π
= 4 × 9
= 36πft³
What is the area of a rectangle with a length of 9 and a width of 17?
Answer:
153 units squared
Step-by-step explanation:
To solve, multiply your length by your width.
[tex]A=lw\\A=9(17)\\A=153[/tex]
Answer:
A=153
Step-by-step explanation:
The area of a rectangle with a length of 9 and a width of 17 is 153.
Formula: A=wl
A=wl=17·9=153
How can 65% be broken down with friendly percents to find 65% of a number?
25% + 25% + 10%
25% + 10% + 10% + 10% + 10%
50% + 10%
50% + 25%
Answer:
The correct ans would be B, 25%+10%+10%+10%+10%
Step-by-step explanation:
When percentages are found, the best way to calculate them is to break them down to the simplest percentage form, and 10% is the simplest percentage that a person can calculate of whatever digit. So if someone wishes to find out the friendly percents, then the easiest would be to calculate the 10% of the figure, add them four times, then add them 2 times plus the half of 10%, which will become 25%, and then add them all to get the 65% of that figure.
Answer:
B.
Step-by-step explanation:
i took the test
What is the value of X ?
Answer:
=14
Step-by-step explanation:
In a rhombus, opposite angles are equal.
In the one provided in the question, 5x° is opposite the angle 70°
Let us equate the two.
5x=70
x=70/5
=14°
The value of x in the figure is 14°
If a graph of y=-4x+2 we’re changed to a graph of y= - 4x+5, how would the y- intercept change ?
The y-intercept would elevate up the y-axis by 3
This is because the y-intercept in y= -4x+2 is 2 and when you change it to y= -4x+5 you are moving the intercept to a y of 5.
what is 7/8 to a decimal rounded to the nearest eighth
[tex]\dfrac{7}{8}=\dfrac{875}{1000}=0.875[/tex]
Answer:
[tex]\large\boxed{\dfrac{7}{8}=0.875}[/tex]
Step-by-step explanation:
[tex]\bold{METHOD\ 1:}\\\\\dfrac{7}{8}=\dfrac{7\cdot125}{8\cdot125}=\dfrac{875}{1,000}=0.875\\\\\bold{METHOD\ 2:}\\\\\dfrac{7}{8}=7:8\qquad\text{divide 7 by 8 (look at the picture)}\\\\7:8=0.875[/tex]
Find the zeros of f(x) = x^2 + 7x + 9
Answer:
-7/2 ±1/2sqrt(13) = x
Step-by-step explanation:
f(x) =x^2 + 7x + 9
To find the zeros, set this equal to zero
0 = x^2 + 7x + 9
I will complete the square
Subtract 9 from each side
0-9 = x^2 + 7x + 9-9
-9 =x^2 + 7x
Take the coefficient of the x term, 7
divide by 2, 7/2
Then square it, (7/2)^2 = 49/4
Add this to both sides
-9 +49/4=x^2 + 7x + 49/4
-36/4 +49/4 = (x+7/2)^2
13/4 = (x+7/2)^2
Take the square root of each side
±sqrt(13/4) = sqrt( (x+7/2)^2)
± sqrt(13) /sqrt(4)= (x+7/2)
± 1/2 sqrt(13) = (x+7/2)
Subtract 7/2 from each side
-7/2 ±1/2sqrt(13) = x+7/2-7/2
-7/2 ±1/2sqrt(13) = x
The function f(x) = x^2 + 7x + 9 has no real-number zeros as the discriminant is negative, indicating that the quadratic formula solution involves an imaginary number.
Explanation:The student is asking to find the zeros of the quadratic function f(x) = x^2 + 7x + 9. To solve for the zeros, we need to find the values of x that make the function equal to zero. We can use the quadratic formula, which is [tex]x = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{{2a}}[/tex], where a, b, and c are the coefficients of the quadratic equation ax^2 + bx + c = 0.
In this case, our equation is already in the correct form with a = 1, b = 7, and c = 9. Plugging these into the quadratic formula, we get:
[tex]x = \frac{{-7 \pm \sqrt{{7^2 - 4(1)(9)}}}}{{2 \cdot 1}}[/tex]
Upon further calculation, we find that the equation has no real-number solutions as the discriminant (b^2 - 4ac) is negative (49 - 36 = 13), leading to an imaginary number in the square root. Therefore, we conclude that the function does not cross the x-axis and has no zeros on the real number line.
Find x if a= 13 and c= 47
Without a specific equation or context, we can't find a specific value for x. If the equation were a+c=x, with a=13 and c=47, then x would equal 60.
Explanation:This question appears to be missing some information to find a specific value for x. If this were an algebraic equation such as a+c=x where a and c are declared as 13 and 47 respectively, you would simply add these two numbers together. So if a=13 and c=47, then x (your answer in this case) would be 60. However, without a given equation or context, it's impossible to determine the exact value for x.
Learn more about Algebra here:https://brainly.com/question/24875240
#SPJ3
what is the value of the natural logarithm when x=3?
Answer:
Step-by-step explanation:
[tex]f(x)=ln(x)\\f(3)=ln(3) = 1.099[/tex]
The weight of 1000 identical samples of a substance are 1 pound. What is the weight of 10 samples?
Answer:
.01 lbs
Step-by-step explanation:
If the weight of 1000 things are 1 pound that means 1 thing has a weight of 1/1000 lbs. So ten things have a weight of 10/1000 lbs or 1/100 lbs or .01 lbs.
From a jar of pennies, 1290 are drawn, marked, and returned to the jar. After mixing,
a sample of 200 pennies is drawn and it was noticed that 50 were marked. Use this
information to predict how many pennies are in the jar.
od to the pain after mising
a) 1,490
b) 258,000
c) 5,160
Answer:
c) 5,160
Step-by-step explanation:
If from a jar of pennies, 1290 are drawn, marked, and returned to the jar and after mixing, a sample of 200 pennies is drawn and it was noticed that 50 were marked. Based on the given information there are 5,160 pennies in the jar.
1290 pennies are drawn and returned to the jar.
200 pennies were drawn.
50 pennies were marked.
1,490 is not enough.
258,000 is way too much.
5,160 makes sense.
Final answer:
Using the proportion of marked to sampled pennies, the total number of pennies in the jar is estimated to be 5160.
Explanation:
The task is to use the information given about the marked and sampled pennies to estimate the total number of pennies in the jar.
This is a classic example of using proportions in mathematics. If out of 200 sampled pennies, 50 are marked, this represents 25% of the sample.
Since 1290 pennies were marked to begin with, we assume that the sampled 25% represents a similar proportion of the total jar.
Thus, the equation to solve is 1290 / total number of pennies = 50 / 200. Simplifying the right side of the equation gives 1290 / total number of pennies = 1 / 4.
By cross-multiplication, the total number of pennies is 4 × 1290, which equals 5160.
I need help with this
Answer:
B
Step-by-step explanation:
Factor the numerator, that is
x² + 6x + 8 = (x + 4)(x + 2), now
f(x) = [tex]\frac{(x+4)(x+2)}{x+4}[/tex]
Cancel the factor (x + 4) on the numerator/ denominator, leaving
f(x) = x + 2 ← simplified version
Cancelling the factor x + 4 leaves a discontinuity ( a hole ) at
x + 4 = 0 ⇒ x = - 4 and f(- 4) = x + 2 = - 4 + 2 = - 2
There is a discontinuity at (- 4, - 2 )
To find the zero let f(x) = 0, that is
x + 2 = 0 ⇒ x = - 2
The zero is (- 2, 0 )
Find the value of the missing coefficient in the factored form of 27f^3 + 125g^3. 27f^3+125g^3=(3f+5g)(9f^2-?fg + 25g)^2
Answer:
15
Step-by-step explanation:
The formula for factoring a sum of cubes is:
[tex]a^3+b^3=(a+b)(a^2-ab+b^2)[/tex]
We have a=3f and b=5g here.
So a*b in this case is 3f*5g=15fg.
The ? is 15.
The value of the missing coefficient in the factored form of the sum of cubes 27f³ + 125g³ is 15, resulting in the complete factorization being (3f+5g)(9f² -15fg+25g²).
The expression 27f³ + 125g³ can be factored using the sum of cubes formula, which is a³ + b³ = (a + b)(a² - ab + b²).
Given [tex]27f^3+125g^3[/tex], we have [tex]a=3f[/tex] and [tex]b=5g[/tex]
Applying the sum of cubes formula, we get:
[tex]27f ^3+125g ^3 =(3f+5g)((3f) ^2 -(3f)(5g)+(5g)^ 2 )[/tex]
[tex]27f ^3 +125g ^3=(3f+5g)(9f ^2-15fg+25g ^2 )[/tex]
So, the missing coefficient in the factored form is 15.
Therefore, the factored form is,
[tex]27f ^3+125g ^3[/tex] is [tex](3f+5g)(9f^ 2-15fg+25g ^2 )[/tex]
The complete question is:
Find the value of the missing coefficient in the factored form of 27f³ + 125g³ .
27f³ + 125g³ =(3f+5g)(9f² -?fg+25g² )
The value of ? =
What is the coordinates of point S?
Answer:
(-0.75, 0.5)
or in fractions:
(-3/4, 1/2)
Step-by-step explanation:
If (s-3)^2=0, what is the value of (s+3) (s+5)?
Here,
(s-3)²=0
→s-3=0
→s=3
Substituting s=3 in,
(s+3)(s+5)
=(3+3)(3+5)
=(6)(8)
=48
The solution to the equation (s-3)²=0 is s=3. Subsequently, the value of (s+3)(s+5) can be calculated by substituting s with 3, giving us the answer 48.
To solve the given equation, (s-3)²=0, we need to find the value of s. This equation means that the value inside the parenthesis, s - 3, when squared equals zero. The only way for a real number squared to equal zero is for that number itself to be zero. Therefore, s - 3 must equal zero. Solving for s, we find that:
s - 3 = 0
s = 3
Now that we know s is 3, we can find the value of (s + 3)(s + 5) by substituting the value of s:
(3 + 3)(3 + 5) = 6 x 8 = 48
Therefore, the value of (s + 3)(s + 5) when (s - 3)² = 0 is 48.
if h(x)=4X^2-16 were shifted 5units to the right and 2 down, what would the new equation be
Answer:
4(x - 5)^2 - 18.
Step-by-step explanation:
For a move 5 to the right f(x) ----> f(x - 5).
For a move of 2 down f(x - 5) ----> f(x - 5) - 2.
For this case we have that by definition of function transformation is fulfilled:
Let h> 0:
To graph [tex]y = f (x-h)[/tex], the graph moves h units to the right.
To graph[tex]y = f (x + h),[/tex] the graph moves h units to the left.
Let k> 0:
To graph [tex]y = f (x) + k[/tex], the graph k units is moved up.
To graph [tex]y = f (x) -k[/tex], the graph moves k units down.
So, we have the following function:
[tex]h (x) = 4x ^ 2-16[/tex]
5 units on the right:
[tex]h (x) = 4 (x-5) ^ 2-16[/tex]
2 units down
[tex]h (x) = 4 (x-5) ^ 2-16-2\\h (x) = 4 (x-5) ^ 2-18[/tex]
Answer:
[tex]h (x) = 4 (x-5) ^ 2-18[/tex]
Bethany wrote the equation X+ (x+2)+(+4)= 91 when she was told that the sum of three consecutive odd integers had a
sum of 91. Which statement about her equation is true?
Bethany is correct because consecutive odd integers will each have a difference of two.
Bethany is correct because there are three xs in the equation and three is an odd number so it represents the sum of odd
numbers.
Bethany is incorrect because 2 and 4 are even numbers, she should use 1 and 3 in their place.
Bethany is incorrect because consecutive integers always increase by 1 each time, not by 2.
Answer:
Option A) Bethany is correct because consecutive odd integers will each have a difference of two
Step-by-step explanation:
The sum of 3 consecutive odd integers is 91. Let the first odd integer is x. The next odd integer will be obtained by adding 2 in x i.e. (x + 2). The third odd integer will be obtained by adding 2 in the second odd integer i.e. (x + 2) + 2 = x + 4
So, the 3 odd integers will be:
x , (x+2) and (x+4)
Their sum is given to be 91. So we can write:
x + (x+2) + (x+4) = 91
Hence, we can conclude that: Bethany is correct because consecutive odd integers will each have a difference of two.
Other options are not correct because consecutive odd integers always increase by 2. For example, the next odd integer after 1 is 3, which is obtained by adding two, similarly the next odd will be 5 and so on.
Answer:
a
Step-by-step explanation:
Suppose an airline decides they are comfortable with excluding the 5% of women with the widest hips. How wide should the airline design the seats using the parameters? Womens hip breadths are normally distributed with a mean of 15.2 inches and a standard deviation of 1.1 inches.
Answer:
17.009 in
Step-by-step explanation:
For a normal distribution with mean of 15.2 in and standard deviation of 1.1 inches, we finnd that 5% are excluded when the width of the seats are greater than 17.009 inches.
Therefore, the seat should have a width of 17.009 in.
To accommodate 95% of women based on hip breadth, airline seats should be designed at least 17.015 inches wide, calculated using the given mean of 15.2 inches, a standard deviation of 1.1 inches, and the z-score for the 95th percentile.
To determine the width of airline seats that would accommodate 95% of women, the airline needs to calculate the 95th percentile of women's hip breadths, modeled by a normal distribution.
Using the provided mean of 15.2 inches and a standard deviation of 1.1 inches, we find the z-score that corresponds to the 95th percentile. In normal distribution, the z-score for the 95th percentile is approximately 1.65.
Using the z-score formula Z =(X - μ / Σ, where Z is the z-score, X is the value we seek, μ is the mean, and Σ is the standard deviation, we can set Z to 1.65 and solve for X:
1.65 = (X - 15.2) / 1.1
X = 1.65 * 1.1 + 15.2
X = approx. 1.815 + 15.2
X = approx. 17.015 inches
Therefore, to exclude only the 5% of women with the widest hips, the airline should design seats that are at least 17.015 inches wide.
Megan paints her locker red, white, and blue.
She paints 9/20 of the locker red, 15% of the
locker white, and 0.4 of the locker blue.
Complete the table below.
Answer:
red: 9/20, 0.45, 45%
White: 15%, 0.15, 3/20
Blue: 0.4, 2/5, 40%
Step-by-step explanation:
For red: you start with 9/20. It’s best to get to a denominator of 10. So divide each number by 2. You would get 4.5/10. Then change to a percent by moving the decimal of the numerator one to the right and changing it to percent. 4.5 -> 45. -> 45%. Then for the decimal, divide 45 by 100. 45/100 = 0.45.
For white: you start with 15%. Divide by 100. 15/100=0.15. Put into a fraction with a denominator of 100. It would be 15/100. Simplify. Each number can be divided by 5, so your fraction would be 3/20.
For blue: you start with 0.4. Turn this into a fraction. Since there is one decimal place, it can have a denominator of 10. The fraction is 4/10, simplified to 2/5. Using the fraction 4/10, the percent would be 40%.
I hope this helps!